An investigation on Mandarin speaking anxiety among non-native Mandarin learners / Ting Hie Ling and Jacqueline Susan Rijeng - Ting, Hie Ling; Rijeng, Jacqueline Susan (Universiti Teknologi MARA , Cawangan Melaka, 2018)
Anxiety is one of the essential factors in Foreign Language learning. It plays a crucial role in determining the performance of students in the target language. Existence feelings of nervousness, anxious, or uncertain while learning foreign language may prevent them from achieving the desired goal and this is what students usually experience in speaking skills. Hence, the aim of the present study is to investigate the level of Mandarin speaking anxiety and the causes of Mandarin speaking anxiety among non-native Mandarin learners. 100 students taking Foundation Mandarin in UiTM Sarawak were investigated to achieve the aim. Foreign Language Classroom Anxiety Scale (FLCAS) was administrated in this study to measure the Mandarin speaking anxiety among non-native Mandarin learners. Statistical package for Social Science (SPSS) was employed to analyze the data. The findings show that non-native Mandarin learners have experienced a certain degree of Mandarin speaking anxiety. The main cause of Mandarin speaking anxiety is speaking Mandarin spontaneously. The findings of this study might help teachers who are engaged in teaching Mandarin as Foreign Language to have a better understanding of how they could help the students to lessen the level of Mandarin speaking anxiety.